Effect of Load Balancing Bonding and Failover on Speed, Latency, Average, and Packet Loss - Toriq, Farhan; Santoso, Banu (Politeknik Negeri Batam, 2024)
This study compares the performance between using load balancing bonding and not using load balancing bonding. This test was conducted on a virtual environment VMware and applied to an Internet Service Provider (ISP) network. The configuration was carried out on two routers connected with three virtual cables that function as load balancing bonding, for the computer to function as a load balancing bonding test. In this study, the workload given consisted of 1000 package. The results of this study showed better performance with load balancing bonding compared to without load balancing bonding, shown in the default condition, the speed with Balance Round Robin mode being higher with a value of 0,157Mbps (Tx) and 3.4Mbps (Rx). Latency with Balance Round Robin mode is smaller with a value of 729ms. The average with Balance Round Robin mode is higher with a value of 768bps. While the packet loss has the same result, namely 0% no lost packets were found. In failover conditions, the speed with Balance Round Robin mode is still higher with a value of 0,107Mbps (Tx) and 2.2Mbps (Rx). The value is